2019
DOI: 10.1007/s11469-019-00100-6
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Gaming Is Associated with Some Health-Related Behaviors Among Finnish Vocational School Students

Abstract: The objective of this work was to examine the connections between problematic digital gaming and various health-related behavior characteristics in a population of vocational school students. Data collection was performed (N = 1335) via an online survey in vocational school units in northern Finland. The survey incorporated the Internet Gaming Disorder Test (IGD10) as well as self-reported measures including questions on socio-demographics, information on the living arrangements of participants, gaming habits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 56 publications
4
15
0
Order By: Relevance
“…Comparison of the latent classes revealed that membership of the class of polysubstance users was positively and mostly-weakly associated with higher levels of GD symptom severity compared to the other classes, and this difference remained significant even after controlling for age, gender, frequency of gaming, and life satisfaction. This pattern is consistent with previous findings, which reported positive (moderate-weak) associations between GD severity and cannabis use and other, unspecific measures of illicit drug use [1,18,40,41]. Similarly, based on a hypothesized U-shaped association between gaming frequency and illicit drug use, a very high level of gaming was positively associated with the use of various types of illicit drugs amongst adolescents, such as marijuana, amphetamines, and MDMA [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Comparison of the latent classes revealed that membership of the class of polysubstance users was positively and mostly-weakly associated with higher levels of GD symptom severity compared to the other classes, and this difference remained significant even after controlling for age, gender, frequency of gaming, and life satisfaction. This pattern is consistent with previous findings, which reported positive (moderate-weak) associations between GD severity and cannabis use and other, unspecific measures of illicit drug use [1,18,40,41]. Similarly, based on a hypothesized U-shaped association between gaming frequency and illicit drug use, a very high level of gaming was positively associated with the use of various types of illicit drugs amongst adolescents, such as marijuana, amphetamines, and MDMA [24].…”
Section: Discussionsupporting
confidence: 91%
“…However, conflicting findings have been reported in the literature when the association between GD and substance use was analysed amongst adolescents. Some of the studies have reported that higher levels of GD were related to earlier onset of alcohol and cannabis use, higher levels of alcohol consumption, cannabis and other illicit drug use, and elevated rates of problems related to alcohol and illicit drug use amongst adolescents [1,[16][17][18][19][20]. On the other hand, various studies have found non-significant and inconclusive relationships (i.e., associations with opposite directions in a longitudinal design) amongst adolescents between levels of GD and alcohol consumption, cannabis use, and related problems [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The 5 types of behavioral risks of electronic games addiction that we have reviewed are the most types of behavioral risks that negatively affect the child, which has clearly increased after the Covid-19 pandemic, this threatens the child with great danger towards this increasing rate of behavioral risks directed against him, which affects his normal relations with his family members. This corresponds to a study ( Karlsson et.al., 2019 ; Männikkö et.al.,2020 ; and Nogueira et al, 2019 ) which emphasized that addiction to electronic games leads to the emergence of aggressive behaviors such as violence and bullying in children, so they have what is called physiological agitation that leads to automatic violence, rebellion, lethargy, and laziness, not hearing instructions and directions from their parents.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that rates of problematic participation in both gambling and video gaming are higher among youth when compared to adults, with 0.2-12.3% reporting problem gambling (PG; Calado, Alexandre, & Griffiths, 2017;Emond & Griffiths, 2020) and 3-10% reporting problem video gaming (PVG; Fam, 2018;Paulus, Ohmann, von Gontard, & Popow, 2018;Stevens, Dorstyn, Delfabbro, & King, 2020). PG and PVG are comorbid with a number of mental health problems including depression, anxiety, impaired sleep, increased substance use and aggression (Lam, 2014;M€ annikk€ o et al, 2020;Mills et al, 2020;Myrseth & Notelaers, 2018). Perhaps unsurprising, both PG and PVG are associated with increased gambling and video gaming frequency, respectively (Carbonneau et al, 2015;Gentile et al, 2011).…”
Section: Problem Gambling and Problem Video Gamingmentioning
confidence: 99%